Extension of the Period of Utilisation of the Perennial Grasses - Chatterjee, B. N.; Singh, R. D. (Indian Forester, 1966)
The green herbage growth (September-October to 7 January) in winter was assessed in three perennial grasses, viz., Andropogon gayanus, Pennisetum polys tachyon and Brachiaria brizantha, grown as spaced plants with 49 kg of P2O5 and 74 kg of N per hectare per annum under rainfed conditions at Ranchi for 3 years (1963-65). Grasses rested from 15-30 September, (after a cut in July) yielded 40-60 q/ha of green herbage with 0.4 to 0.8 per cent nitrogen (dry wt. basis) when cut on 7 January. Andropogon gayanus showed slightly more growth than the others and its leaves were less frost burnt. The plants rested from July and cut on 7 January, except in the case of Brachiaria brizantha, did not yield more than those cut in July, September-October and January. There was not much advantage in green grass growth in winter by leaving 15 em stubbles in autumn over 7.S em stubbles.